Investigating Incursion of Transboundary Pollution into the Atmosphere of Dhaka, Bangladesh - Md. Masud Rana; Mastura Mahmud; Munjurul Hannan Khan; Bjarne Sivertsen; Norela Sulaiman (Advances in Meteorology)
Concentrations of particulate matter (PM) in Dhaka, Bangladesh, during November 2013 to April 2014 were found 7-8 times higher than the World Health Organization (WHO) guideline value. Probability of contribution of transboundary sources to this PM pollution was investigated through different approaches. Ninety-six-hour backward trajectories with every 3-hour interval were computed and clustered into 06 groups based on angle distance matrix. Probabilities of individual cluster to be associated with different ranges of coarse and fine particles were studied. Gazipur station near Dhaka city was found to have 68% probability of receiving PM10 concentration higher than 150 μg/m3 when air masses followed the route of Middle East through the Himalayan valley to the station. This channel was identified as the main route of PM transport to Bangladesh during dry season. Transboundary source-regions were spotted by concentration weighted trajectory (CWT) method and also by the monthly average aerosol optical depths (AOD) over South Asia. North-western Indian regions, Nepal and its neighboring areas, and Indian state of West Bengal were identified as the most probable zones that might have contributed to PM pollution in Gazipur, Dhaka. November to January was the high time the station had experienced fine particles from those transboundary regions.